2018
DOI: 10.1002/hep.30148
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Liver Disease: Outcomes and Risk Factors in a Large Cohort of French Patients

Abstract: CFLD occurs not only during childhood but also later in the lifetime of patients with CF; male sex, CFTR F508del homozygosity, and history of meconium ileus are independent risk factors for CFLD development; earlier use of UDCA over the last 20 years has not changed the incidence of severe CFLD, leading to questions about the use of this treatment in young children given its possible adverse effects. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
2
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 47 publications
3
136
2
6
Order By: Relevance
“…(21) In a recent France study patients with severe CFLD were reported to have worse lung function and nutritional status than other CF patients. (22) However, in our study population, we did find not find a baseline difference in body weight and BMI in CFC patients compared to controls. Our observations therefore do not provide support for improving dietary care in CFC patients as a measure to prevent the increased mortality in these patients.…”
Section: Discussioncontrasting
confidence: 77%
“…(21) In a recent France study patients with severe CFLD were reported to have worse lung function and nutritional status than other CF patients. (22) However, in our study population, we did find not find a baseline difference in body weight and BMI in CFC patients compared to controls. Our observations therefore do not provide support for improving dietary care in CFC patients as a measure to prevent the increased mortality in these patients.…”
Section: Discussioncontrasting
confidence: 77%
“…The majority of CF patients have exocrine pancreatic insufficiency. Endocrine pancreatic insufficiency is seen in approximately 30% of adult patients with a female dominance , CF liver disease in approximately 30% with a male dominance , while osteoporosis and CF arthritis are additional co‐morbidities. These genetic factors, the individual immune response, pharmacometrics as well as lifestyle and socioeconomics influence the treatment of lung infections and the patient's life in general.…”
Section: Co‐morbiditiesmentioning
confidence: 99%
“…Their results are based on a cohort study of 3,328 patients with CF born after 1985 and enrolled in the French CF Modifier Gene Study since 2004, with data collected retrospectively until 2004 and prospectively thereafter. (8) Abbreviations: CF, cystic fibrosis; CFLD, cystic fibrosisassociated liver disease; UDCA, ursodeoxycholic acid.…”
Section: See Article On Page 1648mentioning
confidence: 99%
“…However, the pathogenesis of liver disease presenting in adulthood may be different from that in childhood and, to some extent, unrelated to the CF basic defect. Adult patients may be affected by forms of the noncirrhotic portal hypertension spectrum due to obliterative portal venopathy, as was the case in the population described by Boelle et al Nodular regenerative hyperplasia has been also reported and was possibly related to chronic drug‐induced liver injury from long‐standing antibiotic use . The prevalence and outcome of these conditions need to be better defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation